Modulation of the PGRMC1/NLRP7/HLA-C axis by autophagy is linked to both spontaneous preterm birth and gestational choriocarcinoma - Qin Li; Huaxiao Yu; Dongyi Ling; Jie Zhou; Shanshan Zhen; Yangyang Li; Lijuan Wang; Zetong Zheng; Wenjian Cen; Hongyi Gao; Hui Chen; Jack L. Strominger; et al. (Proceedings of the National Academy of Sciences, 2025)
Spontaneous preterm birth (SPTB) and gestational choriocarcinoma are both associated with complex physiological processes that significantly impact maternal health. While the molecular mechanisms underlying SPTB and gestational choriocarcinoma remain poorly understood, emerging evidence suggests that immune regulation plays a crucial role in both conditions. In this study, we revealed that progesterone regulates autophagy via the noncanonical progesterone receptor membrane component 1 (PGRMC1), which then modulates NLRP7 levels, thereby impacting HLA-C expression in the JEG3 cell line, an extravillous trophoblast (EVT) model. Furthermore, a significant positive correlation between NLRP7 and HLA-C expression was observed in EVTs from placental tissues and choriocarcinoma samples. In cases of SPTB, we found both reduced expression of NLRP7 and HLA-C in EVTs. Similarly, in gestational choriocarcinoma samples, we observed significantly lower expression levels of NLRP7 and HLA-C, further suggesting a shared immune evasion mechanism. These findings not only provide insights into the molecular mechanisms underlying both SPTB and choriocarcinoma but also identify the progesterone-driven NLRP7/HLA-C axis as a promising target for therapeutic intervention, offering strategies for improving outcomes in both conditions.